Meta-Analysis on the Association of C-Reactive Protein Polymorphisms with Metabolic Syndrome - Sharafi, Seyedeh Maryam; Mahdavi, Manijeh; Riahi, Roya; Kheirollahi, Majid; Kelishadi, Roya (Global Medical Genetics, 2020)
Polymorphisms in the C-reactive protein (CRP) genes might have crucial role in the development of metabolic syndrome (MetS). In the current comprehensive meta-analyses, we aim to provide a quantitative assessment of the association between CRP single-nucleotide polymorphisms (SNPs) and the risk of MetS. An electronic search was performed on several databases. After data extraction, random effect model was used to calculate the pooled odds ratio (OR) and 95% confidence intervals (CIs). Four independent studies including case–control, cohort, and cross-sectional methods were analyzed. Our meta-analysis indicated that CRP polymorphisms are not significantly associated with MetS (OR = 0.92, 95% CI = 0.77–1.10) with significant heterogeneity (I2 = 55.4%; p-value = 0.008). The subgroup analysis revealed that only GG has significant association with MetS (OR = 0.32, 95% CI = 0.13–0.80, p-value = 0.015) without significant heterogeneity (I2 = 0%, p-value > 0.05). In conclusion, this meta-analysis provides strong evidence that only some SNPs of CRP gene are associated with the risk for development of MetS; and this relationship does not exist in different ethnic populations.
Keywords: C-reactive protein; single-nucleotide polymorphisms (SNPs); metabolic syndrome; meta-analysis